Factors associated with parental communication with young people about sexual and reproductive health: A cross-sectional study from the Brong Ahafo Region, Ghana. Issue 6 (3rd October 2016) - Manu, Abubakar; Kotoh, Agnes M.; Asante, Rexford Kofi Oduro; Ankomah, Augustine
Abstract : Purpose: Available studies on parent-child communication about sexual and reproductive health in Ghana have largely focused on assessing communication frequency, barriers, and who communicates with whom within the family. The purpose of this paper is to examine parental and family contextual factors that predict parental communication with young people about sexual and reproductive health. Design/methodology/approach: A cross-sectional interviewer-administered survey was conducted among 790 parents selected through a multistage sampling technique. The Cronbach's α statistic was used to assess various parental and family contextual constructs on parent-child communication about sexual and reproductive health. Separate hierarchical multiple regression models for mothers and fathers were constructed to assess predictors of parental communication about sexual and reproductive health. Findings: Nearly the same factors predicted mothers' and fathers' communication with young people about sexual and reproductive health matters. The predictors for both mothers and fathers included high socioeconomic status (SES), family religiousity, parent discipline, perceived parent sexual knowledge and parent trustworthiness. Parent permissiveness predicted only for fathers. Social implications: Parental communication on sexual and reproductive health is influenced by high SES, family religiousity, parent sexual knowledge, parent discipline and trustworthiness. Interventional programmes on communication about sexual and reproductive health need to take cognisance of these factors to improve parent-child communication about sexual and reproductive health. Originality/value: This paper adds to the limited evidence on parent-child communication about sexual and reproductive health in Ghana, by examining parental and family contextual factors that influence parental communication with young people about sexual and reproductive health.